Instagram for business - Butow, Eric; Walker, Corey (--For dummies., 2024)
Become an Instagram aficionado and grow your business online Instagram For Business For Dummies shows you how you can tap into the social media platform with over 1 billion active users and the highest brand engagement of any social app out there. Businesses of all sizes have discovered how successful they can be when they take advantage of Instagram's powerful business tools--including shoppable posts, devoted business profiles, and advanced analytics. This beginner-friendly book helps you take advantage of this great opportunity to connect with a broader audience, tell a gripping story, and make your business an integral part of customers' lives. This new edition covers all of Instagram's latest features, including verified accounts, Broadcast Channels, and integration with Threads. You'll also learn everything you need to know about establishing brand partnerships with influencers, making the most of hashtags, and creating content that will get you noticed. Presented in straightforward language by Instagram and marketing gurus, this book will take you from setting up your account and profile to winning new business on Instagram. Set up your Instagram business account and link your sales to the Instagram Shopping feature Use analytics to understand your engagement and create better content Learn how to effectively use Instagram Stories, Broadcast Channels, and Threads Reach more people with brand partnerships, hashtags, and viral posts Even if you're a complete Insta-beginner, Instagram For Business For Dummies will help you market your brand on this powerful social platform.